DETERMINAN YANG BERHUBUNGAN DENGAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PEKERJA INDUSTRI GENTENG DI KECAMATAN PETANAHAN KABUPATEN KEBUMEN - Azhar Anas; Nur Ulfah; Siti Harwanti (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRAK Musculoskeletal disorders (MSDs) are the complaints on the parts of skeletal muscle is felt by anyone ranging from very mild to very sick complaints. MSDs case data is still high, as many as 141,000 in United Kingdom in the year 2011/2012. The purpose of this study is to determine the determinant related to the complaint Musculoskeletal disorders (MSDs) in the tile industry workers in the District Petanahan Kebumen in 2013. Type and method of this study is observational with cross sectional approach. The total sample of 50 respondents the data obtained through interviews using questionnaires and direct observation. Data analysis is performed using univariate and bivariate (chi square). Results of this study showed that the variables significantly associated with MSDs complaints is workplace risk (p = 0.000), age (p = 0.000), gender (p = 0.000), years (p = 0.000). While the variables are not significantly associated smoking habits (p = 0.392). Suggested workers should do rest for 5 minutes when start to fatigue or stiffness in the muscles of the body. Keywords: Complaints MSDs Kesmasindo, Volume 6, Nomor 2, Juli 2013, Hal 110-115